COMPREHENSIVE MIDWIFERY CARE FOR MRS. R AT THE INDEPENDENT MIDWIFERY PRACTICE OF MIDWIFE IKA ASTUTI, AM,Keb SUBULUSSALAM CITY IN 2026 - Rina Wati; Ningsih; Amra, Ricca Nophia; Bancin, Fitriani; Bancin, Ratna Wati (Mitra Husada Health Internasional Conference (MIHHICo), 2026)
Background: Maternal and infant mortality rates remain critical indicators of public health. Comprehensive midwifery care (Continuity of Care) is essential to reduce these rates through early detection of complications. Objectives: This study aimed to provide comprehensive midwifery care to Mrs. R from pregnancy, labor, postpartum, newborn, to family planning at Ika Astuti AM,Keb Independent Midwifery Practice, Subulussalam City in 2026. Methods: This research used aqualitative case study design with a Continuity of Care (CoC) approach. Data were gathered through interviews, physical examinations, observations, and documentation. Results: Mrs. R's pregnancy progressed normally with mild physiological complaints. Delivery occurred smoothly at 40 weeks of gestation without major complications. Postpartum care and newborn monitoring showed excellent health status, and the mother opted for progestin-only injection contraceptives. Conclusions: Comprehensive midwifery care provided to Mrs. R effectively maintained maternal and neonatal health, showing complete alignment between theory and standard clinical practices.